Rad52 prevents excessive replication fork reversal and protects from nascent strand degradation - Eva Malacaria (Nature Portfolio, 2019)
Stabilisation of stalled replication forks prevents excessive fork reversal and genome instability. Here authors reveal a RAD52-dependent replication fork protection mechanism.